The Impacts of Cooperative Learning on Suburban Students’ Learning Motivation - Arianto, Fajar; Yasin, Fatah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study investigates the impact of cooperative learning on suburban students’ motivation. This study used an experimental approach by comparing the effectiveness of cooperative learning in the experimental group with traditional learning in the control group. The research began by carefully identifying schools in a developing industrial area in Cerme, Gresik City, Indonesia. Data collection was carried out carefully through documentation techniques, including taking various documents and records directly related to student learning motivation. This research group featured 224 high school students divided into two equal groups: 146 students in the experimental group and 145 students in the contr with traditional learning. The data were analyzed using the t-test as an analytical tool to measure and establish the statistical significance of the differences between these two groups of students. The research results clearly show the positive impact of cooperative learning on student motivation, as shown by the p-value of 0.014. In light of these important findings, future research directions have been carefully outlined to include in-depth and longitudinal investigations of motivational sustainability within cooperative learning frameworks, exploration of the potential for cultural variation, refinement of teacher training methodologies, integration of modern educational technologies, and development of parental involvement initiatives and innovative. Cooperative learning can increase student motivation and enrich and stimulate academic environments.